HISTOMETRIC AND ULTRASTRUCTURAL ORGANIZATION OF THE NERVIMUSCULAR TERMINALS OF SKELETAL MUSCLES AT A HYPOKINESIA - Yaschyshyn, Z. M.; Popel, S. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The aim: to study the dynamics of histological and ultrastructural changes in muscle fibers and their neuromuscular endings under conditions of prolonged hypokinesia at different stages of ontogenesis. Methods. Studied skeletal muscles and their peripheral nervous apparatus of laboratory male Wistar rats aged 30 to 270 days. The restriction of motor activity was carried out in special canister cells for 30, 60, 90, and 240 days (5 animals for each term). To determine the type of muscle fiber, the Nahlas histochemical method was used, the Kulchitsky method was used to detect myelinated nerve fibers, the Bilshovsky-Gros method and the electron microscopic method to identify neuromuscular endings. Results. The data of histological and electron microscopic examination of skeletal muscle fibers and their neuromuscular endings under conditions of prolonged hypokinesia indicate their regular restructuring during the development of muscles, the formation of their synapses and structures that are associated with them at different stages of ontogenesis. Conclusion. The study provides an in-depth understanding of the relative frequency and nature of the disturbance of the neuromuscular endings during prolonged hypokinesia and its effect on the dynamics of structural adjustment of individual types of muscle fibers in ontogenesis.